Analisis Manajemen Risiko pada UMKM Konveksi Rumahan NHM Production di Bandung - Nisa Febrianti; Almaira Sarah Junjunan; Sarah Mutia Azahra; Muhammad Shofan Ambiya; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the garment sector play an important role in the economy by providing employment opportunities and meeting society’s demand for clothing products. However, as market competition intensifies, these businesses face various challenges, including changes in fashion trends, quality demands, and rapid technological development. This study, titled “Risk Management Analysis of Home-Based Garment MSME NHM Production in Bandung”, aims to analyze the risks faced by the business and identify effective risk management strategies. The research method used is descriptive qualitative, with data collected through interviews and SWOT analysis. The results indicate that the main risks include operational, financial, human resource, and market risks. Mitigation strategies such as regular machine maintenance, improving production efficiency, and supplier diversification are proven to be effective in minimizing risks. By implementing effective risk management, garment MSMEs like NHM Production can enhance competitiveness and business sustainability.